The 300 Marines: characterizing the US Marines with perfect scores on their physical and combat fitness tests - Looney, David P.; Potter, Adam W.; Schafer, Erica A.; Chapman, Christopher L.; Friedl, Karl E. (Frontiers in Physiology, 2024)
Few US Marines earn perfect 300 scores on both their Physical Fitness Test (PFT) and Combat Fitness Test (CFT). The number 300 invokes the legendary 300 Spartans that fought at the Battle of Thermopylae, which inspired high physical fitness capabilities for elite ground forces ever since.Purpose: Determine distinguishing characteristics of the "300 Marines" (perfect PFT and CFT scores) that may provide insights into the physical and physiological requirements associated with this capability. These tests have been refined over time to reflect physical capabilities associated with Marine Corps basic rifleman performance.Materials and methods: Data were analyzed from US Marines, including 497 women (age, 29±7 years; height 1.63±0.07 m; body mass, 67.4±8.4 kg) and 1,224 men (30±8 years; 1.77±0.07 m; 86.1±11.1 kg). Marines were grouped by whether they earned perfect 300 scores on both the PFT and CFT (300 Marines) or not. We analyzed group differences in individual fitness test events and body composition (dual-energy x-ray absorptiometry).Results: Only 2.5% (n=43) of this sample earned perfect PFT and CFT scores (n=21 women; n=22 men). Compared to sex-matched peers, 300 Marines performed more pull-ups, with faster three-mile run, maneuver-under-fire, and movement-to-contact times (each p<0.001); 300 Marines of both sexes had lower fat mass, body mass index, and percent body fat (each p<0.001). The lower percent body fat was explained by greater lean mass (p=0.041) but similar body mass (p=0.085) in women, whereas men had similar lean mass (p=0.618), but lower total body mass (p=0.025).Marines earning perfect PFT and CFT scores are most distinguished from their peers by their maneuverability, suggesting speed and agility capabilities. While both sexes had considerably lower percent body fat than their peers, 300 Marine women were relatively more muscular while men were lighter.